Aplikasi Kegiatan pada Unit Kegiatan Mahasiswa LP3I Computer Club (UKM LCC) - Rendi Adriandi; Ummu Radiyah; Anton Anton; Esron Rikardo Nainggolan (Faculty of Computer Science, University of Jember, 2020)
The development of telecommunications technology is very rapid along with the times that have reached the era of